Original articleActivation of Akt and Erk pathways in medulloblastoma - Włodarski, Paweł; Grajkowska, Wiesława; Łojek, Magda; Rainko, Kamila; Jóźwiak, Jarosław (Folia Neuropathologica, 2006)
Medulloblastoma (MB) is the most common malignant brain tumour in children. Its aetiology is unknown, although several signalling pathways controlling cell proliferation are thought to participate in the progress of the neoplasm. Mutations of the genes encoding proteins participating in the pathways triggered by embryonic growth factors like Sonic hedgehog (Shh) or WNT are often found in MB. Another model of MB development is overexpression or mutation of several types of growth factor receptors, including IGF-IR, EGF-R and PDGFR, that have the ability to activate cellular kinases responsible for promoting cell proliferation. In order to test this hypothesis, in the current paper we tested the activation of two kinases, Akt/PKB (protein kinase B) and Erk (extracellular signal-regulated kinase) and their substrates in 10 sporadic medulloblastoma cases. We show that MBs are a highly heterogeneous group of tumours that show upregulation of various signalling pathways. Nevertheless, both Akt and Erk may contribute to the progression of MB, triggering, at least in some cases, the mTOR (mammalian target of rapamycin) pathway, controlling translation of several cell cycle-related proteins. We hypothesize that Akt and Erk activation may also be associated with downregulation of protein phosphatase 2A (PP2A).